Dual Cultures of Meloidogyne javanica and Grapevine Rootstocks on Artificial Media - Loubser, J.T.; Meyer, A.J. (South African Journal of Enology and Viticulture, 2017)
Grapevine rootstock cultivars were cultured on more than one artificial medium. Meloidogyne javanica was inoculated on the roots of different cultivars on seven media and penetration and development were recorded. Plate cultures of roots allowed microscopic examination of nematode development. Nematode reproduction occurred on susceptible rootstocks only, suggesting similar results for field and in vitro screening. However, root and nematode development was low and inconsistent, indicating problems which will have to be resolved before general application of the technique.